Delay to first treatment contact for alcohol use disorder. (1st February 2015) - Chapman, Cath; Slade, Tim; Hunt, Caroline; Teesson, Maree
Highlights: We examined patterns and correlates of delay to first treatment contact for alcohol use disorder. We determined the median treatment delay was 18 years (14 years dependence, 23 years abuse). Those with earlier onset and from older cohorts reported longer treatment delays. Those with comorbid anxiety but not mood disorders reported shorter treatment delays. Abstract: Background: This study explored the patterns and correlates of time to first treatment contact among people with alcohol use disorder (AUD) in Australia. Specifically it examined the relationship between sex, birth cohort, onset of AUD symptoms, severity, comorbidity, symptom type and time to first treatment contact (treatment delay) among those with alcohol abuse and dependence in a large population sample. Methods: Data came from the 2007 Australian National Survey of Mental Health and Wellbeing ( N  = 8841). A modified version of the World Health Organization's Composite International Diagnostic Interview was used to determine the presence and age of onset of DSM-IV AUD and other mental disorders and the age at which respondents first sought treatment for alcohol or other drug-related problems. Results: Median time to first treatment contact for an AUD was 18 years (14 years dependence, 23 years abuse). Projected lifetime treatment rates were 78.1% for alcohol dependence and 27.5% for abuse. Those with earlier onset and from older cohorts reported longer delay and were less likely to ever seek treatment compared to those with later onset or from more recent cohorts. Those with comorbid anxiety but not mood disorder, or who reported alcohol-related role disruption or recurrent interpersonal problems were more likely to ever seek treatment and reported shorter delay compared to those who did not report these symptoms. Conclusions: Treatment delay for alcohol use disorder in Australia is substantial. Those with earlier onset and those with comorbid mood disorder should be a target for earlier treatment.